Streptomyces albireticuli lung infection managed as a pulmonary air cyst: a case report and literature review - Liu, Jiajiao; Xu, Zhaoxia; Bai, Yujie; Feng, Jian; Xu, Lunshan; Li, Fuxiang (Frontiers in Cellular and Infection Microbiology, 2024)
Streptomyces, the largest genus in the Streptomycetaceae family and a prolific producer of antibacterial drugs, is a saprophytic soil organism that rarely causes invasive infections. Here we report a case of necrotic pneumonia caused by Streptomyces albireticuli in a 75-year-old man who presented with progressive chest tightness and dyspnea. Streptomyces albireticuli was isolated from his bronchoalveolar lavage fluid and identified through whole-genome sequencing (WGS) and phylogenetic analysis. The patient responded satisfactorily to clarithromycin therapy. The findings of this study may enhance our vigilance in identifying visceral infections caused by Streptomyces.